If Rhodesia had entered the Union in 1922 (Historia, 2021)
An article appeared recently, March 1965, in the 'English magazine History Today in which the author, W. A. P. Phillips, showed how nearl)' 'Nelson intercepted Napoleon on his way to Egypt in 1798 and suggested that the consequences of such an interception might have been very great indeed. Although I do not wish to suggest that the consequences of the incorporation of Rhodesia into the Union would have been comparable to those of an early end to Napoleon's career, nevertheless, in this article I should like to suggest some of the possible consequences for South Africa and Rhodesia, if Rhodesia had accepted the Union Government's offer and entered the Union as a fifth province in 1922
Keywords: Self-Government; Rhodesia; Union Government; Southern Rhodesia; Union of South Africa; South Africa